Identificação dos desperdícios de um serviço de emergência com a utilização da metodologia Lean Thinking - Faveri, Fabiano de (Universidade do Vale do Rio dos Sinos, 2013)
In search of the general improvement of health care organizations in different countries are adopting Lean Thinking. this method consists of a systematic approach to identifying and eliminating waste in production processes, while it has its main focus on adding quality and deliver to the customer only what he sees as value. OBJECTIVE: To identify the different types of existing waste and suggestions for improvements in the emergency department of a private hospital in Caxias do Sul, Rio Grande do Sul, Brazil. METHODS: This is a case study with a qualitative approach, performed in an emergency department a hospital in the city of Caxias do Sul the study sample consisted of 14 professionals working in the emergency department, and 68 flows care of patients. Data collection was conducted observation of workflows associated with conducting focus group. Quantitative data were analyzed using descriptive statistics and qualitative data through content analysis. RESULTS: of the eight types of waste covered by the methodology Lean Thinking, we identified the existence of seven of these, which were wasted by waiting, unnecessary transport and handling, inventory, unnecessary, inappropriate processing, defects and waste of human potential. CONCLUSION: The application of Lean Thinking in the emergency department facilitated the determination of what is actually added value to the service user. Undoubtedly methodology facilitates the visualization of processes and work flows of the patient, providing opportunities for critical analysis of all the steps to search for existing waste reduction.
Keywords: Working environment; Work simplification; Nursing; Health care; Process assessment; Emergency medical services; Ambiente de trabalho; Simplificação do trabalho; ACCNPQ::Ciências da Saúde::Enfermagem